Étude des règles d'indemnisation du préjudice dans l'arbitrage international : vers une indemnisation adéquate du préjudice - Mohamed Gamaleldin, Hossam (Université Paris 1, 2014)
Le recours à l'arbitrage par les opérateurs du commerce international a une finalité très importante, qui est celle de l'indemnisation appropriée et efficiente du préjudice. En vue d'évaluer celle-ci, notre étude adopte une recherche juridique détaillée en matière de réparation pour aboutir à un résultat satisfaisant concernant le principe le plus adapté en tant que cadre commun de l'opération d'évaluation de l'indemnisation du préjudice par les arbitres internationaux, en mettant notamment la lumière sur l'arbitrage CIRDI et CCI. À cette fin, il était nécessaire de suivre une analyse juridique tant sur les règles fondamentales que contingentes de l'indemnisation dans le souci d'avoir une perspective entière du processus de l'évaluation du quantum du préjudice. Un passage transversal était ainsi inéluctable sur les règles juridiques relatives à la réparation en droit privé français ainsi qu'en système juridique de Common Law. Au demeurant, un examen sur la codification de ces règles a été suivi dans le cadre des instruments internationaux de droit uniforme. Toutes ces réglementations ont inspiré le droit de l'arbitrage et ont servi comme des sources de celui-ci en matière de la réparation. Ces développements nous ont conduits à percevoir que l'indemnisation doit être adéquate en prenant en compte non seulement les préjudices subis, conformément au principe général de l'indemnisation intégrale, mais aussi tous les intérêts lésés. Sachant que certains préjudices ne sont pas mathématiquement évaluables, une indemnisation arbitraire s'impose dans ce cas. Un nouveau concept d' « indemnisation adéquate» du préjudice pourrait alors dans l'avenir s'imposer dans le droit de l'arbitrage international.
Keywords: Adequate compensation; Arbitrage international; Damages suffered; Dommages-intérets; Full compensation; Indemnisation adéquate; Indemnisation intégrale; International arbitration; Intérêts lésés; Mercatoria; Prejudices; Process of the evaluation; Processus d'évaluation; Préjudices; Règles d'indemnisation; Réparation (droit international)

La contribution de la commission des Nations unies pour le droit commercial international (CNUDCI) à l'harmonisation et l'uniformisation du droit commercial international - Vieillard, Guillaume (Université de Bourgogne, 2014)
La Commission des Nations Unies pour le droit commercial international (CNUDCI), organe juridique principal de l’Organisation des Nations Unies à vocation universelle, a reçu de l’Assemblée générale de l’ONU pour mandat d’harmoniser, d’uniformiser et de coordonner le droit commercial international. Plus de quarante-cinq années après sa création, la CNUDCI poursuit son œuvre dans les domaines les plus importants du droit commercial international tels que l’arbitrage commercial international, la vente internationale de marchandises, le droit des sûretés, l’insolvabilité, les paiements internationaux, le transport international de marchandises, le commerce électronique, la passation de marchés et le développement des infrastructures. En adoptant divers instruments juridiques par le biais d’un processus de négociation intégrant les Etats ainsi que certaines organisations intergouvernementales et non gouvernementales, la CNUDCI met à la disposition de la communauté internationale des marchands les outils juridiques nécessaires permettant de faciliter et de sécuriser les opérations du commerce mondial. La présente thèse analyse la manière dont la CNUDCI contribue au renforcement du droit commercial international en adoptant un ensemble de règles juridiques sur les opérations commerciales internationales.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; CNUDCI; Commerce international; Compétence normative; Coordination; Droit commercial (droit international); Droit commercial international; Harmonisation; Harmonization; International trade law; Modernization; Nations unies. Commission pour le droit commercial international; Normative action; UNCITRAL; Unification internationale; Uniformisation

Modernizing and harmonizing international contract law: the CISG and the Unidroit Principles continue to provide the best way forward - Dennis, Michael J. (Uniform Law Review, 2014)

O diálogo sustentável entre o direito do comércio internacional e o direito à água - Vieira, Andréia Costa (Universidade de São Paulo, 2014)
O Direito Internacional Contemporâneo é um sistema pluralista e tem se defrontado com temas os mais diversos na atual agenda internacional. Um dos temas que têm merecido a preocupação do Direito Internacional é a chamada crise da água, assim entendida como a escassez, a poluição, a crise de abastecimento, a sede do setor privado para entrar nesse mercado e os diversos conflitos internacionais em torno da água. A problemática da água envolve, principalmente, três áreas distintas do Direito Internacional, a saber: o Direito do Comércio Internacional, o Direito Internacional do Meio Ambiente e o Direito Internacional dos Direitos Humanos. Para lidar com essa problemática e trazer soluções concretas à questão da água, a presente pesquisa sugere um diálogo entre essas distintas áreas do Direito. Parte do pressuposto do Direito Internacional como um sistema, apesar dos seus distintos regimes, identificando-o frente ao fenômeno da globalização e seu consequente fenômeno da governança global, emoldurado por distintos atores internacionais, distintas normas de direito e distintos fóruns de aplicação. Apresenta o Regime do Comércio Internacional e o Regime do Meio Ambiente Internacional, nos quais já se inserem as questões hídricas, e identifica possíveis diálogos entre esses regimes, moldados pela noção de desenvolvimento sustentável. Afirma a existência do Regime Internacional da Água Doce e suas duas bases de construção estrutural e desenvolvimento: o Direito Internacional da Água Doce para fins diversos da navegação e o Direito Humano à Água. Apresenta os elementos de cada uma dessas defesas e conclui pela existência e desenvolvimento desse regime, cuja consolidação deve ser feita através de um diálogo com o Regime do Comércio Internacional. Nesse proposto diálogo, apresenta dois tipos de interação entre regimes: a interação conflitual e a interação relacional. Como interação conflitual, faz dialogar as normas do GATT e do GATS com as normas do Regime Internacional da Água Doce. Como interação relacional, traz propostas concretas que harmonizam o comércio internacional e a proteção das águas doces, a saber: a criação de uma agência especializada, no âmbito da ONU, para assuntos hídricos; a criação de uma Convenção Quadro sobre recursos hídricos e a criação de um Mecanismo de Desenvolvimento Limpo para a água e seu consequente mercado de water certificates. Após detalhar esse hibridismo das normas sobre recursos hídricos, conclui pela legitimidade dessa interação relacional e pelos ganhos que podem advir em favor de um desenvolvimento sustentável, através desse diálogo entre o Direito do Comércio Internacional e o Direito à Água. The contemporary International Law is a pluralistic system that has faced distinct issues in the contemporary international agenda. One of these issues is the so termed water crisis, which comprises scarcity, pollution, water supply matters, the eagerness of the private sector to dominate it and the different international water conflicts. Water issues have mainly evolved through three different subjects of International Law: International Trade Law, International Environmental Law and International Law of Human Rights. To deal with these issues and to bring about real solutions to the water crisis, this research suggests a dialogue between these three different law subjects. It starts with the conjecture that International Law is a system, despite its different regimes, and identifies it within the phenomenon of globalization and its consequent phenomenon of global governance - shaped by distinct international actors, distinct rules and distinct adjudication fora. It presents the International Trade Regime and the International Environmental Regime, within which the water issues can be found, and points out possible dialogues between these regimes, shaped by the notion of sustainable development. It affirms the existence of the International Freshwater Regime and its two structural and developmental bases: the International Law of Non-Navigational Uses of Watercourses and the Human Right to Water. It introduces each element of these two subsystems and it concludes for the existence and development of the International Freshwater Regime, whose consolidation should be built on a dialogue with the International Trade Regime. Within such a proposal of dialogue, it presents two kinds of regime interaction: a conflict interaction and a relational interaction. As a conflict interaction, it brings about a dialogue between the GATT and the GATS rules and the International Freshwater Regime rules. As a relational interaction, it points out real instruments to harmonize international trade law and freshwater protection: the creation of a specialized agency under the United Nations auspices; the creation of an umbrella-convention on water resources; and the creation of a clean development mechanism and its consequent water certificates market. After explaining the hybridism of the water resources rules, it concludes for the legitimacy of this relational interaction and the gains it may have towards a sustainable development through a dialogue between International Trade Law and the Right to Water.
Keywords: Abastecimento de água; Commerce international; Comércio internacional; Dialogue of sources; Direito comercial internacional; Direito das águas; International law regimes; Recursos hídricos; Right to water; Trade of water; Água doce

International sales contracts in Congolese law : a comparative analysis - Kahindo, Nguru Aristide (University of South Africa, 2014)
To regulate and facilitate are the main functions of legal rules. These purposes are achieved by a harmonised legal system by which the law becomes identical in numerous jurisdictions. The process to unify the law of sale internationally started in the 1920s and culminated, in 1988, in the implementation of the CISG. This Convention intends to provide clarity for most international sales transactions by regulating the formation of contracts, and the rights and obligations of the seller and the buyer resulting from the contract. The CISG has these days enjoyed much ratification and influenced a number of legislation reforms worldwide. Despite the role it played during the drafting process of the CISG, the DRC has not yet ratified it. Instead, the country continued to rely, until recently, on colonial legislations which had become out-dated, and inadequate to meet modern international sales contracts requirements. The situation appears to have been improved a year ago as the effect of the adoption of OHADA law whose Commercial Act is largely inspired by the CISG. Because the introduction of OHADA law in the DRC is very recent, this study intends to assess the current state of Congolese sales law by comparing it with the CISG and South African law, which is non-CISG but modernised. The comparative study aims at establishing whether current Congolese law, as amended by OHADA law, is sufficient or has shortcomings; if it has some, it aims to identify those shortcomings, and make suggestions for their improvements. After discussion, it has been discovered that the ratification of OHADA law has significantly improved Congolese domestic sales law. Given that there remain certain unresolved shortcomings in Congolese international sales law, however, the study ends by a proposal for the accession of the DRC to the CISG in order to fill them.
Keywords: Congo (Democratic Republic); Congolese contract law; Congolese sales law; Contracts; Export sales contracts; Formation of the contract; International sales law; OHADA law; Obligations of the buyer; Obligations of the seller; Sale of goods; South Africa; South African contract law; South African sales law

Regulating trade in petroleum under the WTO Regime: trade rules vs. reality of the petroleum industry - Bitenov, Gani (McGill University, 2014)
This thesis critically assesses the effectiveness of WTO legal rules in the regulation of international trade in petroleum and highlights potential conflicts between competing resources of energy from the WTO regime’s perspective. The theoretical framework of the thesis is built on the concepts used in natural resource economics, trade theories and international relations. On the basis of Hotelling’s rule of natural resource economics, it proposes a model that reconciles the use of petroleum and the development of renewable sources of energy in the power generation sector, which prospectively can be adopted with respect to the transport sector and other sectors involving energy use. The proposed model may improve global sustainable development. However, it is argued that WTO rules are not properly designed to regulate trade in petroleum and, if applied without due respect to specific issues pertaining to the petroleum industry, would obstruct the achievement of the social optimum, and detrimentally affect the national economies of WTO members and global welfare in general. To improve the WTO system, I propose a reformation of its normative ideology through the introduction of the strategic trade policy theory in complement to the neoclassical theory of trade, at least when trade in energy is concerned. On the basis of the study of the applicability of WTO rules to trade in petroleum and a review of proposals put forward by other scholars to improve the regulation of trade in energy, it is argued that the most effective way to improve the trading regime is to negotiate a new general agreement on trade in energy.The role of the WTO in the regulation of trade in energy is analyzed through a regime management theory borrowed from international relations studies. It is argued that the WTO as a regime manager is capable of improving the regime by properly maintaining the existing equilibrium and by initiating, and leading in negotiations of a new equilibrium.
https://escholarship.mcgill.ca/concern/theses/ws859j68h
Keywords: Petroleum industry and trade; Trade regulation; WTO trade rules

Three theories of Lex Mercatoria - Cuniberti, Gilles (Columbia Journal of Transnational Law, 2014)

Verkäufer und Käufer im Spiegel regionalen und universalen Einheitsrechts - Tchameni, Joseph-Augustin (Universität Wien, 2014)
Die Koexistenz des „regionalen" und „universalen“ Einheitsrechts wirft eine Reihe von Rechtsfragen auf, deren Behandlung und Lösung auf den Gebieten des Privat- und Wirtschaftsrechts nicht nur Schwierigkeiten bereiten, sondern auch erhebliche Umstellung erfordern. Einerseits bietet der wachsende Bestand regional vereinheitlichter oder harmonisierter Rechtsnormen gegenüber dem disziplinären Rechtswesen des Völkerrechts ein anderes, facettenreiches Bild und bringt damit neue Forschungsweisen sowie ein anderes Denken und Wissen im Bereich des Privat- und Handelsrechts hervor. In der Erforschung der Spannungsverhältnisse und Lösungsansätze, die sich aus Wechselwirkungen, Konkurrenzverhältnissen sowie Konfliktlagen zwischen derartigen Rechtswesen ergeben, stehen die Rechtswissenschaften noch am Anfang. Andererseits führt die Entwicklung der elektronisch unterstützten Gestaltung sämtlicher wirtschaftlicher Transaktionen (E-Commerce) einen Wandel in der Wirtschaft herbei. Der Kauf von Waren bei einem Online-Versandhaus, die elektronische Kommunikation zwischen einer Handelskette und ihren Zulieferbetrieben, Teleshopping, die elektronische Unterstützung von Warentransporten stellen Beispiele für diesen Wandel dar. Der Internetzugang erleichtert die Intensivierung des An- und Verkaufs von Waren über staatliche Grenze hinweg. Bei derartiger „Grenzenlosigkeit“ wirtschaftlicher Nutzung und aufgrund der fortschreitenden Globalisierung stellt sich im Zuge des Geschäftsverkehrs zwischen Unternehmern (Kaufleuten) oder zwischen Unternehmer und Verbraucher als Parteien aus rechtlicher Sicht neben den unverzichtbaren vertraglich zu regelnden Punkten auch die Frage nach dem auf den Kaufvertrag anwendbaren Recht. Aus dieser Perspektive analysiert die Arbeit umfassend und kritisch gegenüber , - nach einer systematischen Darstellung des UN-Kaufrechts und der(s) OHADA (Rechts insb AU.DCG) hinsichtlich der Entstehung, des Aufbaus, der Grundzüge, der Bedeutung unter Berücksichtigung des Verhältnisses zwischen den beiden Regelwerken und deren Eigenschaften -, den Kaufvertrag zwischen dem Verkäufer und dem Käufer ins System des Handelskaufs der OHADA im Vergleich zu CISG-Regelungen.
Seller and bayer in the mirror of regional uniform law and universal uniform law https://phaidra.univie.ac.at/detail/o:1311737
Keywords: AUDCG; Acheteur; OHADA; Seller and buyer in the mirror of regional; Uniform law; Universal uniform law; Universalen Einheitsrechts; Vendeur; Verkäufer und Käufer im Spiegel regionalen